Brazil : neoliberalism versus democracy - Saad-Filho, Alfredo, 1964-; Morais, Lecio (PlutoPress, 2017)
A political analysis of the paradox of modern-day Brazil, charting the political transition from military rule to democracy, and to neoliberalism.